2021
DOI: 10.1016/s2352-3018(21)00157-0
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and immunogenicity of the ChAdOx1 nCoV-19 (AZD1222) vaccine against SARS-CoV-2 in people living with and without HIV in South Africa: an interim analysis of a randomised, double-blind, placebo-controlled, phase 1B/2A trial

Abstract: Background People living with HIV are at an increased risk of fatal outcome when admitted to hospital for severe COVID-19 compared with HIV-negative individuals. We aimed to assess safety and immunogenicity of the ChAdOx1 nCoV-19 (AZD1222) vaccine in people with HIV and HIV-negative individuals in South Africa. Methods In this ongoing, double-blind, placebo-controlled, phase 1B/2A trial (COV005), people with HIV and HIV-negative participants aged 18–65 years were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
146
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(170 citation statements)
references
References 20 publications
(49 reference statements)
15
146
3
3
Order By: Relevance
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies assessed anti-SARS-CoV-2 immunity through an immunoassay to detect antibodies targeted at the spike protein, including some targeting specifically the receptor-binding domain (RBD) of the spike protein. Thirty studies reported neutralization assay results in addition to anti-SARS-CoV-2 antibody assays [ 34 , 37 , 41 , 48 , 51 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ]. Thirty-one studies provided data on cellular immunity [ 17 , 21 , 22 , 34 , 37 , 41 , 45 , 46 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 72 , [74] , [75] , [76] , [77] , [79] , [80] , [81] , [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to HIV-uninfected persons of the same age, there were no differences in humoral and cell-mediated immune response after 56 days of follow-up [ 28 ]. An interim analysis of the COV005 trial in South Africa for the same vaccine showed that two doses were well tolerated with similar neutralizing response patterns in PLWH and HIV-negative participants [ 29 ]. A prospective study of the BNT162b2 (Pfizer) vaccine conducted in 143 virologically suppressed PLWH with high CD4 T-cell count found that 97% developed anti-RBD-IgG in this group, while 98.9% did in the control group.…”
Section: Covid-19 Vaccine Outcomes In Plwhmentioning
confidence: 99%
“…cepas variantes e menor distanciamento social e uso de medidas protetoras 7,8 . Observou-se uma redução da eficácia das vacinas de mRNA (Pfizer e Moderna) em relação à prevenção de infecções sintomáticas pelo coronavírus de cerca de 95% para 65% em trabalhadores da área da saúde 8 .…”
Section: Referênciasunclassified